Potential Analysis of Quercetin and Its Derivatives as Inhibitors of Hendra Virus (HeV) - Rosyiidah, Nur Anisa; Setiarso, Pirim; Sanjaya, I Gusti Made (Universitas Negeri Medan, 2024)
This study aims to determine the inhibitory potential of quercetin and its derivatives on the activity of Hendra virus (HeV) 6BK6 protein with its comparator N-Acetyl-D-[1-13C] Glucosamine. This research was carried out using the molecular docking method in order to obtain information related to binding affinity values, inhibition constants, and amino acid residues in the ligand-receptor hydrogen bonds. It was found that the compound quercetin 3-O-xyloside had the lowest binding affinity among the other compounds, namely -6.92 kcal/mol with an inhibition constant of 8.44 µM. In addition, there are four types of amino acid residues in the ligand-receptor hydrogen bonds including ASP304 (1,90 Å), SER301 (2,47 Å), ARG191 (3,18 Å), and MET188 (4.34 Å). In this case it can be concluded that the compound quercetin 3-O-xyloside has been shown to have the potential to inhibit the activity of the HeV 6BK6 protein.